Cross Cutting Affiliation Moderating Ethnic Socialisation Influence Towards Social Distance Amongst Indonesian Chinese Students in Jakarta and Surabaya (Architecture Image Studies, 2026)
As a multi-ethnic country, Indonesia will always face the challenge of social distance amongst its ethnicities. The multicultural setting has made each ethnicity possessing a different culture. This means that each ethnicity does not only perceive itself differently but also has a different perception towards the others. Such diversities made each ethnicity has its own ‘life world’. ‘Life world’ includes religious cultural traditions, collective memories, relation forms, and solidarity values inheritance. One of the most common discussed social distance issues is between Indonesian Chinese (Tionghoa) and non-Indonesian Chinese. Previous studies noted the relation between social distance with ethnic identification. Ethnic identification consequently is attached with ethnic socialisation. However, the high ethnic awareness does not automatically produce ethnic bias. The circumstance resulted due to cross-cutting affiliation. Our research focuses on such issues. This study was conducted in Jakarta and Surabaya due to the multi-ethnicities’ nature of the two cities. We employ confirmatory quantitative method as our research method in examining ethnic socialisation, social distance, and cross-cutting affiliation. We have 266 respondents (68.8% female and 31.2% male) who are Indonesian Chinese students and 18-23 years old for this research. Our research reveals the negative impacts of ethnic socialisation towards social distance as well as the role cross-cutting affiliation as moderator variable. The Indonesian Chinese youth respondents in this research show significant social distance towards non-Indonesian Chinese ethnicities. Such notable social distance resulted from the negative impacts of their ethnic socialisation experience. The most distinguished element from ethnic socialisation is cultural socialisation. The existence of cross cutting affiliation can lessen the negative impacts.